Analisis Multimedia Interaktif Pembelajaran Membaca, Menulis, Berhitung Pada Paud KB Adzkia - Khofifah Fauzani; Myra Thasandra; Pauji Wibowo; Ali Ikhwan (CV. ITTC INDONESIA, 2023)
Advanced information technology and high speeds of communication technology within global networks will be used extensively in the future of information technology. The service information system can be published into a more interesting and real form within multimedia information form, and it can also be easy to manage and use for personal computers with the support of advanced high-speed computer systems and the fundamentals of multimedia technology. The Luther (Sutopo, 2003) method, which is a process that assists the software developer in forming a model from the software that must be made, is used in the peripheral development of multimedia applications. Adobe Photoshop, Adobe Director, Adobe Flash, and processor application voice Sony Vegas are all used in this application making, with the assistance of processor media draw, animation, and authoring. Students can learn and comprehend how to read, write, and calculate with the assistance of interactive learner multimedia that is supported by a computer. Children can use one of these interactive multimedia to learn how to read, write, and calculate. These multimedia programs combine animation, video, games, and other media with information for reading, writing, and math. Children can understand and learn from the material by comparing it to real-world examples through the use of virtual images. This interactive multimedia for students was packaged on compact discs that can be used with a computer. PAUD KB ADZKIA's interactive multimedia program specifically designed for children in the PAUD grade. With the current version of this application, we hope to provide a benefit to the child and the other learning media.